Yarn hairness and diameter characterization using a CMOS line array - Carvalho, Vítor (2008)
This paper presents a new system for determining yarn hairiness and diameter using a CMOS linear array together with a data acquisition board and custom developed software. The final image is generated using coherent optical signal processing with a Fourier high-pass spatial filter. The system was previously tested and validated in simulation using an image analysis line profile tool. Several analyses were performed in a laboratorial environment testing different yarns. Finally, the results obtained with this new system are compared to those obtained previously using a simple photodiode in place of the linear photodiode array. The new system is more precise although the data processing requires significant computational effort.